'Information War' as the Russian Conceptualisation of Strategic Communications. Issue 1 (2nd January 2020) - Fridman, Ofer
Abstract : The Kremlin employs a type of 'strategic communications', which, according to the Russian conceptualisation of information war, is a combination of military and non-military means intended to influence the information-psychological space of a targeted audience. Ofer Fridman argues that the Kremlin's employment of economic counter-sanctions (non-military means) and its intervention in Syria (military means) demonstrate the Kremlin's capability to participate in information war – the Russian counterpart of Western strategic communications.